Odpowiedź :
1.
[tex]\frac{2x+5}{6}[/tex] + [tex]\frac{5x-10}{4}[/tex]- [tex]\frac{x}{1}[/tex]=0
[tex]\frac{4(2x+5)}{24}[/tex] + [tex]\frac{6(5x-10)}{24}[/tex] - [tex]\frac{24x}{24}[/tex]=0
[tex]\frac{8x+20+30x-60-24x}{24}[/tex]=0 /*24
8x+20+30x-60-24x=0
14x-40=0
14x=40 /:14
x= [tex]\frac{40}{14}[/tex]
x= 2[tex]\frac{6}{7}[/tex]
2.
[tex]\frac{x+3}{5}[/tex]-[tex]\frac{4-x}{2}[/tex]-1=0
[tex]\frac{2(x+3)}{10}[/tex]-[tex]\frac{5(4-x)}{10}[/tex]-[tex]\frac{10}{10}[/tex]=0/*10
2x+6-20+5x-10=0
7x-24=0
7x=24/:7
x= 3 [tex]\frac{3}{7}[/tex]
3.
[tex]\frac{1-2x}{3}[/tex]+[tex]\frac{14}{10}[/tex]-1=0
[tex]\frac{10(1-2x)}{30}[/tex]+[tex]\frac{42}{30}[/tex]-[tex]\frac{30}{30}[/tex]=0 /*30
10-20x+42-30=0
-20x +22=0
-20x= -22/*(-1)
20x= 22 /:20
x= 1 [tex]\frac{2}{20}[/tex]
x= 1 [tex]\frac{1}{10}[/tex]